Development of a physical education learning model and play-based approach for improving students' fundamental movement skills - Mega Rezkya; Hendri Neldi; Aldo Naza Putra; Ahmad Chaeroni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop a game-based Physical Education, Sports, and Health (PJOK) learning model that is valid, practical, and effective in improving the fundamental movement skills of fourth-grade students at SD Negeri 13 Pasaman. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants included one content expert, one media expert, 15 PJOK teachers, and 43 fourth-grade students. Data were collected through validation sheets, practicality questionnaires, and fundamental movement skill tests. Data analysis involved descriptive statistics, paired-samples t-tests, and N-Gain analysis. The developed model met the criteria of validity, practicality, and effectiveness. Content expert validation reached 95%, while media expert validation achieved 80%. Practicality assessments yielded scores of 92% from teachers and 98% from students. The paired-samples t-test indicated a significant improvement in students’ fundamental movement skills (p < 0.001), and the N-Gain score was 0.7475, categorized as high. The game-based PJOK learning model is valid, highly practical, and effective for improving elementary students’ fundamental movement skills and is suitable for implementation in physical education learning.